Nucleocapsid protein structures from orthobunyaviruses reveal insight into ribonucleoprotein architecture and RNA polymerization - Ariza, A; Tanner, S; Walter, C; al., E (Oxford University Press, 2013)
All orthobunyaviruses possess three genome segments of single-stranded negative sense RNA that are encapsidated with the virus-encoded nucleocapsid (N) protein to form a ribonucleoprotein (RNP) complex, which is uncharacterized at high resolution. We report the crystal structure of both the Bunyamwera virus (BUNV) N–RNA complex and the unbound Schmallenberg virus (SBV) N protein, at resolutions of 3.20 and 2.75 Å, respectively. Both N proteins crystallized as ring-like tetramers and exhibit a high degree of structural similarity despite classification into different orthobunyavirus serogroups. The structures represent a new RNA-binding protein fold. BUNV N possesses a positively charged groove into which RNA is deeply sequestered, with the bases facing away from the solvent. This location is highly inaccessible, implying that RNA polymerization and other critical base pairing events in the virus life cycle require RNP disassembly. Mutational analysis of N protein supports a correlation between structure and function. Comparison between these crystal structures and electron microscopy images of both soluble tetramers and authentic RNPs suggests the N protein does not bind RNA as a repeating monomer; thus, it represents a newly described architecture for bunyavirus RNP assembly, with implications for many other segmented negative-strand RNA viruses.